(R)‐Tonkafuranone and related compounds: Improved synthesis, stereochemical purity in nature, and bioactivities of the pure enantiomers. (21st June 2019) - Hoffmann, Matthias; Mufusama Koy Sita, Jean‐Pierre; Kleider, Carolin; Gunesch, Sandra; Rothmund, Bruno; Lehmann, Leane; Bringmann, Gerhard; Decker, Michael
Abstract: Dehydromenthofurolactone (tonkafuranone) and other bicyclic lactones are common flavour compounds and can be found in a variety of plants. Herein, we present an improved synthesis of the natural product and a series of close analogues, in combination with efficient purification methods for simple preparation from cheap and easily accessible chemicals. A two‐step, one‐pot, reaction procedure, consisting of an aldol condensation step with concomitant lactonization, yields simplified analogues of the natural parent compound ( R )‐tonkafuranone and its likewise natural ( S )‐enantiomer, lacking one or two of its methyl groups, respectively. In the case of regioisomeric products, these were resolved by preparative high‐performance liquid chromatography, which, in the case of chiral, yet racemic products, was followed by preparative enantio‐resolution on a chiral phase, permitting the isolation of all four pure isomers from one synthetic step. Using the stereo‐analytical method developed, the enantiomeric purity of natural tonkafuranone occurring in Bursera graveolens was analysed and found to be '100:0' in favour of the S ‐enantiomer. The chiral, enantiomerically pure products were configurationally assigned by co‐elution, semi‐synthesis, and/or chiroptical methods. With the pure isomers obtained, specific cytotoxicities were tested in two cell lines as a measure for their reactivities towards cellular nucleophiles. Although the synthesized compounds differed in their cytotoxic potential in V79 cells, they exhibited a much smaller cytotoxic potential than the mutagenic α, β, γ, δ‐unsaturated lactone patulin. No toxicity towards murine hippocampal HT‐22 cells was observed at 50 μM. Thus, the molecular mechanism contributing to the high reactivity of patulin towards nucleophiles may not apply for tonkafuranone and structurally related compounds. Abstract : The synthesis of dehydromenthofurolactone (tonkafuranone) and demethylated derivatives thereof was conducted in a one‐step procedure followed by the separation of the regioisomers and enantiomers with HPLC and identification with CD spectroscopy. Derivatives were bioevaluated regarding their cytotoxicity showing demethylation at C‐3 enhances toxicity.